Bending Versus Transforming the Drug Cost Curve: A Matter of Political Will. Issue 4 (July 2020) - Major, Ajay; Polite, Blase N.
Abstract : Abstract: There is increasing consensus that comprehensive reforms are needed to curb the rising costs of specialty drugs and growing bipartisan agreement on the basic principles that these reforms must address (1) constraints on yearly inflation of drug prices, (2) limits on practices to extend patents and restrict generic competition, (3) increased transparency of rebates provided by pharmaceutical companies to pharmacy benefit managers and insurance companies, and (4) caps on the total yearly out-of-pocket costs for Medicare patients. While such reforms will improve the current system, they are unlikely to be truly transformative. Transformative change requires that all the relevant stakeholders be forced, by a legislative or administrative mandate, to come to an agreement on value. Whether federal policy makers have the will to do so will determine whether we truly change the trajectory of the currently unsustainable drug cost curve.